DISCOURSE IN ANTHROPOCENTRISM - Aliqulova Xolniso Urol qizi (TADQIQOTLAR, 2026)
Abstract.This article explores the concept of discourse within the framework of anthropocentrism and analyzes the role of the human factor in language and communication. The study explains how discourse reflects human thinking, cultural values, worldview, and communicative intentions. Special attention is given to the anthropocentric approach in modern linguistics, where language is studied in close relation to human cognition and social interaction. The article also discusses the connection between discourse, context, and culture, emphasizing that every type of discourse carries traces of human perception and experience. Ultimately, the paper highlights the importance of discourse analysis in understanding the relationship between language, thought, and society from an anthropocentric perspective.